TINJAUAN KRIMINOLOGI TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DI KABUPATEN BULELENG - Kadek Hendra Wirawan; I Wayan Landrawan; Si Ngurah Ardhya (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
The purpose of this study is to examine and analyze the factors that cause the occurrence of criminal acts of sexual violence against children and the prevention efforts made by law enforcement officers. The type of research used is an empirical legal research type with a descriptive research nature. The location of this research was conducted in Buleleng Regency. Data collection techniques used are document studies, observations and interviews. The sampling technique used is the Non Probability Sampling technique and the subject determination using the Purposive Sampling technique. Qualitative data processing and analysis techniques. The results of the study indicate that the factors causing the crime of sexual violence against children in Buleleng Regency are caused by internal factors and external factors. The internal factors consist of weak self-control and the perpetrator's morale. While the external factors are family factors, environmental factors and technological development factors. The efforts to overcome the crime of sexual violence against children are carried out with pre-emptive (non-penal), preventive (non-penal) and repressive (penal) efforts, namely by providing legal understanding to the community and establishing a good cooperative relationship with the community and conducting various kinds of supervision. As well as efforts made by conducting investigations and investigations in accordance with applicable legal provisions, using forensic assistance, carrying out all kinds of actions according to procedures.